Exploring the Link Between Adverse Childhood Experiences and Adolescent Dating Violence Perpetration and Victimization: A Review of the Literature - Katie N. Russell; Laura A. Voith; Ashley S. Withrow (Youth)
Background and Purpose: Adverse childhood experiences (ACEs) have been linked with multiple adverse outcomes, including adolescent dating violence (ADV). ADV is a serious public health issue, with the U.S. rates ranging from 6.4% to 73% for victimization across all types and from 11% to 77% for perpetration. Given the high prevalence of ADV and the fact that it has been frequently linked with ACEs earlier in life, it is crucial to thoroughly understand this relation and apply this information to prevention and intervention efforts. However, to date, there are no known reviews synthesizing the link between ACEs and ADV, nor exploring which ACEs have been included across other studies. Methods: To address these gaps, this study included three comprehensive searches to identify the following: (1) the measurement tools used to measure ACEs; (2) the type of ACEs significantly linked with ADV; and (3) the risk and protective factors considered in this relation. Results: A total of 34 studies were included. There were 24 different assessment tools used to measure the ACEs of adolescents, with the number of ACEs included ranging from 1 to 93. All but one study linked at least one ACE to ADV. The types of ACEs linked with ADV consisted of victimization (e.g., child abuse and bullying), witnessing violence (i.e., home and school), and household dysfunction (e.g., caregiver substance abuse). Several risk and protective factors were considered. Conclusions/Implications: This study found the measurement of ACEs in the literature to be inconsistent, making it difficult to synthesize and compare the findings across studies. Despite the measurement inconsistencies, however, most studies linked ACEs with ADV, emphasizing the importance of considering this relation in prevention/intervention programming.